Effects of Nonuniform Blade Pitch on the Flow Through an Annular Turbine Nozzle - Rainer Kurz (International Journal of Rotating Machinery)
This paper discusses flow measurement results both upstream and downstream of a transonic annular gas turbine nozzle with a nonuniform pitch. The downstream measurements are performed in the plane where the leading edge of the rotor blade is located in the gas turbine. The experiments were performed using total pressure probes and wall static pressure taps. The pitch variation modifies the flow field both upstream and downstream of the nozzle, although the experiments show that the effect is localized to the immediate neighborhood of the involved blades. The effects on the wakes and on the inviscid flow are discussed separately. The mean velocities show a strong sensitivity to the changes of the pitch, which is due to a potential flow effect rather than a viscous effect.